Electrotechnological system for monitoring effects of optical range electromagnetic fields on vegetation bioobject - Nikiforova, L.; Kizim, I.; Bogatyrev, Yu. (Технічна електродинаміка, 2014)
The question of application of sources of light on light-emitting diodes in hothouses is considered. The necessity of development of complex for registration of bioelectric potentials of plants, necessity for working off technology of growing of plants with the use of lamps on light-emitting diodes is grounded. The developed measuring complex allows to influence on vegetable bioobjects with LED (laser) SOR and to estimate the response in real time. Size of BEP reflects real processes of a metabolism and is inseparably linked with a physiological condition of a live organism, and the steady nonequilibrium state in vegetable organisms is supported due to processes of a metabolism continuously proceeding in them. Thus, at research of various ways of stimulation of development of VBO measurement of size BEP can be used for an assessment of a functional condition of VBO at different stages of an organogenesis.